Hygienic practices and associated factors in slaughterhouses and meat retail shops in Hawasa City, Ethiopia - Lakew Desta Zewude; Embialle Mengistie; Amanuel Ejeso (PLoS ONE, 2025)
Background In developing countries, animals are often slaughtered and dressed in unsanitary settings, thus endangering the microbiological quality and safety of the meat obtained. In addition, slaughterhouses and retail outlets are the regions most vulnerable to cross-contamination with meat. As a result, the objective of this study was to evaluate slaughterhouse and meat retail shop hygiene practices and to determine the causes of unsanitary meat handling in slaughterhouses and retail shops. Methods 165 butcher men from a municipal slaughterhouse and every retail meat store in Hawassa city participated in this investigation, which was carried out using an institution-based cross-sectional study design between March 22 and May 30, 2022. Data was collected through interviewer-administered standardized questionnaires and an observation checklist. Data was entered using Epidata software version 3.1.1, and it was exported for further analysis using SPSS version 25. A cutoff point of P.V < 0.25 was employed for the bivariate model to control possible confounders. A binary logistic regression analysis was conducted to identify independent factors, the findings were displayed as the 95% confidence interval for the crude odds ratio and adjusted odds ratio. The level of significance was assessed using cutoff points of P < 0.05. Results The prevalence of good hygienic practices was 25.5% [95% CI: (18.2–32.1)]. Attitude (fair attitude) [AOR = 0.157; 95% CI: (0.037, 0.659)], cleanness and disinfection of waste container status [AOR = 12.64; 95% CI: (3.936–40.562)], regular supervision by health offices [AOR = 0.176; 95% CI: (0.35–0.894)], health and safety training [AOR = 3.46; 95% CI: (1.054–11.344)], and Removal of personal items during meat processing [AOR = 0.036; 95% CI: (0.008–0.150)] were factors that were significantly associated with poor hygienic practices. Conclusion The prevalence of good hygienic practices was low. After adjusting for possible confounding factors, attitudes, cleanness and disinfection of waste containers, regular supervision by health offices, health and safety training and Removal of personal items during meat processing (behavioral factor) were significantly associated with hygienic practices. These findings could call for appropriate prevention strategies based on cognitive domains and practice.